Association between physical activity and mild cognitive impairment in community-dwelling older adults: Depression as a mediator - Liu, Xinya; Jiang, Yihua; Peng, Wenjia; Wang, Meng; Chen, Xiaoli; Li, Mengying; Ruan, Ye; Sun, Shuangyuan; Yang, Tingting; Yang, Yinghua; Yan, Fei; Wang, Feng; et al. (Frontiers in Aging Neuroscience, 2022)
Dementia has become a public health priority and is irreversible. Mild cognitive impairment (MCI), an intermediate state between normal cognition and dementia, is the prime time for early diagnosis and intervention. The activities of daily living of dementia patients are usually insufficient. Therefore, continuing to explore the risk factors of MCI, especially the influence of physical activity on MCI and its mechanism can enrich the relevant research fields in China. For this cross-sectional study, 2518 adults aged 60 years or older in Xinzhuang, Minhang District, Shanghai were recruited between July 2019 and April 2019, using a multistage, cluster-sampling method. A binary unconditional logistic regression model was used with MCI status as the dependent variable. Different types of physical activity were separately included in the multifactor model to test their correlations. Sensitivity analysis was performed using BADL as a stratification factor. The mediating effect of depression between physical activity and MCI was examined using the Bootstrap method. This research includes 271(10.8%) MCI. Old age (odds ratio 2.967 [95%CI 2.063~4.269]), having diabetes (1.816 [1.302~2.534]), and depression (3.012 [2.209~4.108]) were possible risk factors for MCI. High education level (0.722 [0.523~0.999]), medium level of physical activity (0.459 [0.326~0.645]), and high level of physical activity (0.396 [0.270 ~0.580]) were possible protective factors. Medium (0.548 [0.396~0.757]) and high levels (0.557 [0.366~0.846]) of physical exercise and medium (0.433 [0.318~0.590]) and high levels (0.487 [0.296~0.801]) of household chores are possible protective factors of MCI and their significance remained in the mutually adjusted model. Sensitivity analysis showed that physical activity and household chores were possible protective factors in all strata (P<.05). Physical exercise and work-related activities showed a protective effect in fully independent older adults, but the effect disappeared in those who cannot be fully independent. Depression played a partially mediating role with an indirect effect of 6.67%. Overall, our results highlight that physical activity is a possible protective factor for MCI. Physical exercise and household chores have strong protective effects and future interventions could be targeted from this perspective. Depression plays a partially mediating role and more attention should be paid to the mental health of older adults.